The Interviewer as Partisan: American Journalists in Conversation with Fidel Castro - Renzo Llorente (Études Caribéennes)
Following the triumph of the Cuban Revolution in 1959, many US reporters, including some of the best-known names in American journalism (such as Barbara Walters and Dan Rather), had the opportunity to interview Fidel Castro. All of the resulting interviews, which range from relatively brief exchanges to book-length texts, served as contributions, to one degree or another, to Americans’ perception of Fidel Castro and, more generally, to Americans’ conception of the Cuban political system and US-Cuba relations. Given the high caliber of many of the journalists who interviewed Fidel, one would naturally assume that said contributions consist, by and large, of well-informed, unbiased, enlightening interviews with the leader of the Cuban Revolution. But is that what we really find in these interviews?A careful analysis of interviews with Fidel Castro by major US journalists reveals that well-informed, unbiased, enlightening interviews are in fact the exception, rather than the rule. Indeed, most of these journalists’ interviews with Castro—such as those of Lisa Howard (1963); Barbara Walters (1977); Robert MacNeil (1985); Maria Shriver (1988); and Tom Brokaw (1995)—follow a surprisingly similar script: the interviewer focuses on alleged human rights abuses in Cuba; treats Cuba’s political institutions and practices with skepticism; insists on knowing what concessions Cuba is prepared to make to the United States; implicitly criticizes Cuba’s foreign policy and—prior to 1990—Cuba’s relationship with the Soviet Union; neglects to consider the validity of Cuba’s complaints about US policy; and, in general, suggests that the US government’s aggressive attitude toward Cuba is justified in light of the policies pursued by Castro. As a result, in interviewing Fidel many prominent and influential American journalists did little more than justify and perpetuate the attitudes and policies toward Cuba of successive US governments—something that becomes quite apparent when one contrasts these journalists’ endeavors with the major interviews conducted by well-known journalists from other nations who also had the chance to converse with Castro. In sum, far from enhancing the American public’s understanding of Revolutionary Cuba, many high-profile US journalists actually reinforced some of the very misconceptions, distortions and elements of misinformation that have long constituted an important barrier to a healthier relationship between the United States and its Caribbean neighbor.